A hidden link between leaf development and senescence. (November 2018) - Koyama, Tomotsugu
Highlights: Developmental stage-dependent consequences of ethylene on leaves. Roles of developmental regulators in leaf senescence. Regulatory modules intertwined in leaf morphogenesis/differentiation and senescence. Abstract: Leaf senescence is the final step of leaf development and is usually accompanied by visible color changes from green to yellow or brown. Unlike the senescence of the whole body of animals and unicellular organisms, which is often associated with death, leaf senescence in plants requires highly integrative processes towards cell death with nutrient recycling and storage. Since leaf senescence plays pivotal roles in the production of plant biomass and grain yield, the mechanisms of degradation and relocation of macromolecules as well as the regulation of signaling and biosynthetic pathways have received much attention. The importance of the plant hormone ethylene in the onset of leaf senescence has been clearly documented. However, research has increasingly demonstrated that the function of ethylene in the regulation of leaf senescence is dependent on leaf development. This review raises the issue of how ethylene requires developmental regulators and focuses on the developmental aspect of leaf senescence. It also emphasizes the remarkable impact that developmental regulators have on regulating the onset of leaf senescence.